Pushback after backsliding? Unconstrained executive aggrandizement in the Philippines versus contested military-monarchical rule in Thailand. Issue 1 (2nd January 2021) - Thompson, Mark R.
ABSTRACT: How do different kinds of democratic backsliding affect opposition pushback? To contribute to the answer, this article compares two divergent cases in the Asia-Pacific – "executive aggrandizement" in the Philippines and a "promissory" military coup in Thailand. An institutional explanation focused on remaining electoral, state institutional, and civil societal forms of democratic accountability despite autocratization does not elucidate significant variations in pushback. In the Philippines, elections have been fairer, state institutions less obviously manipulated and restrictions on civil society less overt. But opposition pushback has been significantly weaker than in Thailand despite more generalized repression and institutional manipulation there. An alternative explanation examines how opposition pushback is influenced by regimes' efforts to legitimize autocratization. Thailand's military-monarchical rulers had little success in framing recent elections as democratic while legitimacy linked to the monarchy has also eroded. This has catalysed the formation of a broad civilian opposition alliance, with strong parties, regular protests and critical social media. By contrast, while the Philippines' Rodrigo Duterte acts illiberally, he claims continued democratic legitimacy based on competitive elections and high opinion ratings while ruling largely constitutionally. This has undermined electoral opposition and weakened civil society, with no sustained protests and activists out-"trolled" on social media.